GOOD CORPORATE GOVERNANCE DI SEKTOR KEUANGAN: DAMPAK GCG TERHADAP KINERJA PERUSAHAAN (Kasus di Bursa Efek Jakarta) - Sukmawati Sukamulja (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2004)
Corporate governance has become an issue of global significance. The improvement of corporategovernance practices is widely recognized as one of the essential elements in strengthening the foundationfor the long-term performance of countries and corporation. It has also been linked to the broader issuesof national governance and action against corruption at all levels of society within the economicframework of countries. In business, investors would pay a substantial premium for well governedcompanies. Indonesia as one of the emerging countries needs to implement the good corporate governanceto cope with the global economy. The stream of interest in this empirical research examines theapplication of good corporate governance in companies based on annual report that affects to thecompany’s market value, measured with Tobin’s Q.